Optical and magnetic investigation of Cu doped ZnO nanoparticles synthesized by solid state method. (2022) - Vasudevan, J.; Johnson Jeyakumar, S.; Arunkumar, B.; Jothibas, M.; Muthuvel, A.; Vijayalakshmi, S.
Abstract: The pure and different parentage of copper doped ZnO nanoparticles were synthesized by solid state method. The synthesized nanoparticles were characterization of XRD, SEM, FT-IR, UV–Vis and PL technique. The XRD studies exhibited the good crystalline nature in different nanometer range crystal size with different doping percentage of copper. SEM micrograph shows that the well- dispersed highly agglomerated, accompanying almost well-defined crystalline nature and rod shaped ZnO nanoparticles. The PL spectra for ZnO (pure) and Copper doped ZnO nanoparticles is the formation of a new broad peak at 505 nm arises from the widening or redshift effects of the pre-existing peak at 381 nm. This confirms the enhanced visible light optical activity observed with (8%) Cu-ZnO-Nanoparticles.